Properties of High-Performance Concretes made of Black Sand at High Temperature - Eltawil, Khaled A.; Tahwia, Ahmed M.; Mahdy, Mohamed G.; Abdelraheem, Ahmed H. (Civil Engineering Journal, 2021)
To modify high-performance concrete (HPC) fireproofing properties, black sand (BS) was partially substituted as fine aggregate at various levels. This study aims at evaluating the BS reliability in improving HPC durability properties for various construction applications based on its unique heavy minerals. To achieve this, five HPC series blends were setup to substitute fine aggregate independently with BS. Substitution percentages ranged from 15 to 100% with consistent supplementary cementing materials (SCMs) proportion for each gathering. Tests were performed to assess compressive strength before and after fire exposure under various temperatures of 250, 500 and 750 °C at different curing age. Generally, blending FA with BS was better than using SF with BS. Utilizing BS in the range of 15 to 60% as fine aggregate with 10% FA improves HPC fire-insulating properties. Besides, Z1 SEM analysis observed homogenously and compacted HPC microstructure at 250 and 500 °C. Doi: 10.28991/cej-2021-03091634 Full Text: PDF